2021
DOI: 10.1371/journal.pone.0252937
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Polish version of the Motivational Postures (Toward Taxes) Questionnaire

Abstract: This article presents a Polish adaptation of the Motivational Postures (Towards Taxes) Questionnaire (MPQ). The MPQ is based on the concept of five tax-related motivational postures (Commitment, Capitulation, Resistance, Disengagement and Game Playing) and consists of 29 items. Three studies validating the Polish version of the MPQ are presented. The first study was conducted with a translated version of the original questionnaire and aimed to verify the factorial validity of this version using confirmatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The six-factor solution is presented in Table 2. Five out of the six factors align with findings from previous studies (Braithwaite, 2003;Kołodziej, 2021). Two dimensions of compliance emerged: commitment and capitulation.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The six-factor solution is presented in Table 2. Five out of the six factors align with findings from previous studies (Braithwaite, 2003;Kołodziej, 2021). Two dimensions of compliance emerged: commitment and capitulation.…”
Section: Resultssupporting
confidence: 84%
“…In total, 12 items were adapted into Spanish from various motivational postures scales (Bartel & Barclay, 2011;V. Braithwaite, 2003;Kołodziej, 2021;Murphy & Cherney, 2012;Sargeant et al, 2021), while 11 items were specifically created for this study, taking into account the Spanish-speaking context. It is worth noting that the proposed scale was developed by the research team and assessed by a group of independent experts who suggested modifications, all of which were incorporated.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation